Integrative and Complementary Health Practices for Chronic Pain: summary of clinical guideline recommendations - Marcus Tolentino Silva; Daniel Miele Amado; Paulo Roberto Sousa Rocha; Jorge Otávio Maia Barreto (Epidemiologia e Serviços de Saúde)
Abstract Objective To evaluate the recommendations of clinical guidelines that used the Grading of Recommendations Assessment, Development and Evaluation system (GRADE) for Integrative and Complementary Health Practices in the management of chronic pain in adults. Methods A summary of evidence based on rapid review, in an agile, rigorous, and timely manner, to inform health decision-making. Searches were conducted in Medline, Embase and Scopus, and included clinical guidelines that assessed the quality of evidence and the strength of recommendations. The methodological quality of the guidelines included was assessed using the Appraisal of Guidelines for Research & Evaluation II tool, aiming to characterize how well-founded and transparent the included guidelines were. Results Eighteen guidelines published between 2011 and 2024 were included, eight of which were of high methodological quality. The most recommended practices were acupuncture, osteopathy, chiropractic, yoga, tai chi, meditation, and relaxation techniques, for conditions such as low back pain, chronic pelvic pain, fibromyalgia, irritable bowel syndrome, chronic pancreatitis and rheumatoid arthritis. The quality of the evidence supporting these recommendations was predominantly low to moderate, with recommendations overwhelmingly weak. The interventions were considered effective and had a favorable safety profile compared to conventional treatments. Strong recommendations included acupuncture, osteopathy, chiropractic, and yoga for low back pain. Conclusion The quality of the evidence was limited, suggesting the need for further robust studies of interventions for chronic pain management. Acupuncture, osteopathy, chiropractic and yoga presented better evidence, with potential for effectiveness and safety for the Brazilian Unified Health System.